Stabilization of Two Electricity Generators - Dany Ivan Martinez; José de Jesús Rubio; Arturo Aguilar; Jaime Pacheco; Guadalupe Juliana Gutierrez; Victor Garcia; Tomas Miguel Vargas; Genaro Ochoa; David Ricardo Cruz; Cesar Felipe Juarez (Complexity)
In this research, a sliding mode regulator with sine mapping is suggested for the stabilization of electricity generators being affected by magnet interaction nonlinearities and generator nonlinearities. To reach this goal, our suggested regulator has the following contributions: (a) it starts from the sliding mode regulator with the modifications that the saturation mapping is used to reach a smoother performance instead of the signum mapping, and the sine mapping is applied to reach an upper bound in the proportional gain error, (b) it is used to reach some chosen constant behaviors for the angle position, angle speed, and current in the electricity generators, and (c) its stabilization is ensured based on the Lyapunov approach. We show the simulation of the suggested regulator in two electricity generators.